Event planner - Lim, Mun Jun (2015)
This project is divided into two parts: firstly it is the understanding of the role and job scope of an event planner; secondly it is the event management software that allows planners to plan with ease. Event planners work to ensure that a common purpose is being achieved. Common purpose such as meetings, conventions and any private functions that brings people together. Planners have to coordinate and execute every details, from the speakers and venues/locations to arranging of agenda materials and audio-visual equipment depending on the details related to the variety of meetings, conventions and private functions. Planner have to be able to understand the needs of his/her client or organization and organize an event just for them. Understanding the requirement(s) and creates a program or a list of agenda that addresses the purpose, message or impression that the client or organization will like to bring across to the floor. Along the way with which the planner’s experiences, expertise, skills and knowledge like details-oriented and organization management will be accumulated. Event planning software is a tool that allows event planner to do budgeting, activities forecast, keeping planners and client on track with their focus. The software allows planners to update whatever is required from the client with simple touches, amend and edit clients’ requirement at your fingertips. With the software, planner can easily access to real-time database from various hotels or venues regarding the rates and availability via the internet. In other words, the software helps the planner to keep track of even the miniscule details of the events and keep the planner in focus with the project schedule.